PENGARUH LOAN TO DEPOSIT RATIO DAN RETURN ON ASSETS TERHADAP PRAKTIK WINDOW DRESSING PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2018-2021 - Silalahi, Evelin Roma Riauli; Sembiring, Yan Christin Br; Purba, Imelda Rimenda; Zalukhu, Lian Martinline; Lumban Gaol, Romasi (UNIKA Santo Thomas, 2023)
This study aims to determine the effect of Loan to Deposit Ratio and Return On Assets on Window Dressing practices in Banking Sector Companies for the 2018-2021 period. The population used in this study was Window Dressing, Loan to Deposit Ratio, and Return On Assets with 46 banking sector companies and the sample of this study was 112 obtained from 28 banking sector companies multiplied by 4 years. The data used in this research is secondary data obtained from the website www.ojk.go.id during the period 2018 to 2021. The data collection method uses documentation. The data analysis used is multiple regression analysis test. Based on the results of the analysis performed, it can be concluded that the variable Loan to Deposit Ratio partially has no effect on Window Dressing practices with a significant value of 0.090 > 0.05 and Return On Assets partially has no effect on Window Dressing practices with the acquisition of a significant value of 0.887> 0.05. In addition, it simultaneously has no effect on Window Dressing practices with a significant value of 0.117 > 0.05.